Cortactin in Epithelial–Mesenchymal Transition - Ji, Rong; Zhu, Xiao-Juan; Wang, Zhi-Rong; Huang, Li-Qiang (Frontiers in Cell and Developmental Biology, 2020)
Cortactin, a member of the actin-binding protein family, plays an important role in cell movement involving the cytoskeleton, as cell movement mediated by cortactin may induce the epithelial–mesenchymal transition. Cortactin participates in tumor proliferation, migration, and invasion and other related disease processes by binding to different proteins and participating in different pathways and mechanisms that induce the occurrence of these disease processes. Therefore, this article reviews the correlations between cortactin, the actin cytoskeleton, and the epithelial–mesenchymal transition and discusses its clinical importance in tumor therapy.